1990
DOI: 10.1159/000243240
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Macromolecules and Epithelial Cell Surface Glycosylation in Suckling Rats Nursed on Mothers Fed Low-Protein Diet-I

Abstract: The effect of feeding 8 % protein (low-protein; LP) diet to lactating rats has been studied on the absorption of macromolecules and the glycosylation of enterocytes in suckling animals. The absorption of 125I-labelled bovine serum albumin, γ-globulin and α-lactalbumin was 24–314% more in pups nursed on mothers fed LP diet compared to the pair-fed controls. The observed enhancement in protein absorption was associated with a significant increase in the binding of these proteins to microvillus membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Since surface oligosaccharides are well known to act as receptors ETHANOL AND MICROVILLUS MEMBRANE GLYCOSYLATION 141 for toxins and to participate in the adhesion of microorganisms in the intestinal lumen [3], it is likely that changes in MVM glycosylation could influence the quantity and quality of microflora in the intestine. Receptor-mediated endocytosis may also be affected under such dietary regimens [31].…”
Section: Discussionmentioning
confidence: 99%
“…Since surface oligosaccharides are well known to act as receptors ETHANOL AND MICROVILLUS MEMBRANE GLYCOSYLATION 141 for toxins and to participate in the adhesion of microorganisms in the intestinal lumen [3], it is likely that changes in MVM glycosylation could influence the quantity and quality of microflora in the intestine. Receptor-mediated endocytosis may also be affected under such dietary regimens [31].…”
Section: Discussionmentioning
confidence: 99%
“…High-fat diets induce an increase in the sialo/sulfomucins ratio of colonic mucins in mice . In other studies, both fat and protein levels in the human diet have been shown to modulate intestinal glycosylation. , Restriction of dietary threonine significantly inhibits synthesis of intestinal mucins while vitamin A supplementation impacts the expression of numerous extracellular matrix proteins (ECM) including laminin, collagen, elastin, fibronectin, and proteoglycans . A deficiency in vitamin A is detrimental to the intestinal barrier reducing levels of MUC2 and defensin-6 expression, while also enhancing MUC3, TLR2, and TLR5 expression …”
Section: Introductionmentioning
confidence: 99%